Cognitive stimulation therapy as a sustainable intervention for dementia in sub-Saharan Africa: Feasibility and clinical efficacy using a stepped-wedge design – ERRATUM. (3rd April 2017) - Paddick, Stella-Maria; Mkenda, Sarah; Mbowe, Godfrey; Kisoli, Aloyce; Gray, William K.; Dotchin, Catherine L.; Ternent, Laura; Ogunniyi, Adesola; Kissima, John; Olakehinde, Olaide; Mushi, Declare; Walker, Richard W.
Abstract : In the above article (Paddick, 2017 ) The corresponding author's details were previously listed incorrectly. The correct details are; contact number +44 191 293 2709 and email addressWilliam.gray@nhct.nhs.uk . The original article has been updated with the correct contact details. The publishers apologise for any inconvenience and confusion this error has caused.